2019
DOI: 10.1177/0963689719860840
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Induces Release of Smaller Extracellular Vesicles from Porcine Mesenchymal Stem Cells

Abstract: Mesenchymal stromal/stem cells (MSCs) belong to the endogenous cellular reparative system, and can be used exogenously in cell-based therapy. MSCs release extracellular vesicles (EVs), including exosomes and microvesicles, which mediate some of their therapeutic activity through intercellular communication. We have previously demonstrated that metabolic syndrome (MetS) modifies the cargo packed within swine EV, but whether it influences their phenotypical characteristics remains unclear. This study tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…The current study shows that obesity alters the size and miRNA cargo of human ASC-derived EVs. The number of EVs released from lean-and obese-ASCs was similar, but obese-EVs were smaller compared to lean-EVs, in line with our previous observations in swine obese-EVs (Conley et al, 2019). miRNAs upregulated in obese-EVs target preferentially clusters of genes participating in regulation of NF-kB and MAPK signaling, cytoskeleton organization, and apoptosis, whereas miRNAs downregulated in obese-EVs target groups of genes implicated in cell cycle, angiogenesis, and MAPK and Wnt signaling.…”
Section: Discussionsupporting
confidence: 91%
“…The current study shows that obesity alters the size and miRNA cargo of human ASC-derived EVs. The number of EVs released from lean-and obese-ASCs was similar, but obese-EVs were smaller compared to lean-EVs, in line with our previous observations in swine obese-EVs (Conley et al, 2019). miRNAs upregulated in obese-EVs target preferentially clusters of genes participating in regulation of NF-kB and MAPK signaling, cytoskeleton organization, and apoptosis, whereas miRNAs downregulated in obese-EVs target groups of genes implicated in cell cycle, angiogenesis, and MAPK and Wnt signaling.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we have also shown that MetS can modify the cargo and size of porcine adipose tissue-derived MSC, including mRNAs, miRNAs, and proteins, which might in turn control some important cellular functions (15,16). In addition, the transcriptome and proteome of particularly genes in MSCs involved in mitochondria, inflammation, and transcription regulation were found to be altered in MetS (17).…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, MetS-induced changes in the content and function of adipose tissue-derived MSCs may also impact on their EV progeny. Recently, we reported that swine MetS altered the size distribution of MSCderived EVs compared with those obtained from lean pigs toward smaller vesicles packed with genes commonly associated with exosomes (8), although the overall EV number released by MetS MSCs remained unchanged. MetS also modulates the mRNA cargo packed within porcine adipose tissue MSC-derived EVs, which contain genes involved in translational regulation and modulation of inflammation (39).…”
Section: Cardiovascular Risk Factors and Evsmentioning
confidence: 90%